The IL-4 Paradox: How an Anti-Inflammatory Cytokine Fuels Prostate Cancer Progression - Ibnu Widya Argo; Raden Danarto; Tanaya Ghinorawa; Indrawarman Soerohardjo (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
Prostate cancer is one of the most prevalent malignancies in mern worldwide, with complex immune interactions contributing to tumor progression. In contrast, benig prostatic hyperplasia (BPH) is a non-cancerous enlargement of the prostate that dos not exhibit malignant behavior. Understanding the molucelur differences between benign and malignant prostate condition is essential, particulary regarding immune escape mechanisms that allow cancer cells to evade the immune system. Interleukin-4 (IL-4), an anti-inflammatory cytokine, has been implicated in modulating immune responses within the Tumor Microenvironment. This study was conducted using a retrospective, observational analytical design with a cross-sectional approach to investigates the relationship between IL-4 expression and apoptosis-associated immune checkpoint receptors (PD-1, CTLA-4) and their ligand (PD-L1, PD-L2) in prostate tissue. A total of 40 formalin-fixed, paraffin-embedded (FFPE) prostate tissue samples collected between 2014 and 2020 were analyzed using quantitive real-time PCR (qRT-PCR). Samples were categorized into four groups: BPH, non-metastatic prostate cancer, metastatic prostate cancer, and controls. Statistical analysis was performed using one-way ANOVA and Pearson correlation. IL-4 expression was significantly higher in prostate cancer tissues (both metastatic and non-metastatic) compares to BPH (p = 0.006). Among the immune checkpoint molecules, IL-4 showed the srongest correlation with PD-L1 (r = 0.919), followed by PD-L2 (r = 0.832) and PD-1 (r = 0.626). In the BPH group, CTLA-4 exhibited the highest ecpression, with IL-4 ranked second. In conclusion, IL-4 expression is closely associated with key immune checkpoint markers in prostate cancer, suggesting a potential role in promoting immune escapen and tumor progression. Keyword: Prostate Cancer, IL-4, PD-1, CTLA-4, PD-L1 and PD-L2.